Exploring Marital Satisfaction Through the Lens of Psychology and Islamic Perspectives - Furqon, Muhammad Arif; Zain, Nabilah Kamiliyah (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Marriage, a significant life milestone, holds profound importance in both human experience and Islamic belief, representing fulfillment, love, and sacred duty. However, achieving marital satisfaction, crucial for a fulfilling union, encompasses multifaceted factors, including communication, conflict resolution, and shared responsibilities. This study employs a Systematic Literature Review method to explore marital satisfaction from psychological and Islamic perspectives. Psychological research emphasizes interpersonal dynamics, communication, and problem-solving skills, while Islamic teachings underscore tranquility, affection, and adherence to divine guidance. By integrating insights from both perspectives, this study offers a comprehensive understanding of marital satisfaction, shedding light on its essence, indicators, and the interplay of human endeavor and divine guidance in nurturing a harmonious marital bond.